The Potential Of Honeycomb Bait in Increasing Catches Results Of Umbrella Fish Traps in Teluk Merbau Village - Br. Sihite, Dumeria; Hutagalung, Pinia; Enjelina, Putri Dewi (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
Teluk Merbau Village is a village that is included in small scale fisheries by fishing using umbrella fish traps. The potential catches in umbrella fish traps gear in Teluk Merbau Village is not optimal. Based on this, this study was conducted with the aim of identifying the potential influence of honeycomb bait on the catches of umbrella fish traps in Teluk Merbau Village. In this study, a comparative descriptive analysis method was used by calculating the composition of the main catch and discard catch on 6 umbrella fish traps using honeycomb bait and without bait. The results of this study show that there is a difference in the number of catches between honeycomb bait and no bait with a catch of 5,5 kg with bait and 3 kg without bait. The catch showed that honeycomb bait had the potential to increase the proportion of the main catch by 18% with a percentage of 91% with bait compared to no bait by 73%. The main catch obtained consisted of jerbung shrimp (Penaeus merguiensis) and rock shrimp (Metapenaeus ensis). These findings provide an indication that honeycomb bait can be an alternative bait that supports the optimization of fishermen's catches.